Biophysical Characterization of the Membrane-proximal Ectodomain of the Receptor-type Protein-tyrosine Phosphatase Phogrin - Noguera, Martín Ezequiel (2013)
The receptor-type protein-tyrosine phosphatase (RPTP) phogrin is localized at the membrane of secretory granules of pancreatic islet ;-cells and, similarly to the closely related ICA512, plays a role in the regulation of insulin secretion, in ensuring proper granulogenesis and stability, and in the regulation of -cell growth. The mature membraneproximal ectodomain of phogrin (MPE phogrin) was produced as a recombinant protein and characterized. CD, fluorescence, controlled proteolysis, size-exclusion chromatography, and multi-angle light scattering showed that it is a properlyfolded monomeric domain. Equilibrium experiments, in the presence of guanidinium chloride and thermal unfolding, suggest a two-state mechanism with a G of 2.3-3.3 kcal/mol, respectively. The study establishes common features and differences of MPE phogrin and the homologous ectodomain of ICA512. A homology model of phogrin was built based in the x-ray structure of MPE ICA512. The model is a starting point for modeling the entire receptor and for testing the quaternary structure and interactions of this protein in vivo. A description of the membrane insertion mode and putative interacting surfaces of this large protein is fundamental for the understanding of its biological function.